Empreendedorismo. Soluções Inovadoras para Questões Sociais - Isabel Cristina Ferraz Barros (Desenvolvimento em Questão, 2013)
This article aims to identify associations between the dimensions of entrepreneurial attitude in the context of social entrepreneurs. Characterized as a descriptive study with a quantitative approach. The population was composed of 36 managers of social organizations registered with Volunteer Partners Organization. It was used as a tool for data collection, a structured questionnaire applied to the managers of the participating organizations. For data analysis, descriptive statistics were analyzed and Pearson correlation matrix. The main results showed a predominance of females and the main reason for the choice of entrepreneurial activity, there was the need to promote community / people in need and living with another entrepreneur. The results showed positive correlations of moderate to high between entrepreneurial attitude and its dimensions, with emphasis on the social dimension, where the results were significant in almost all indicators.